Managing Group Conflict and Decision-Making Skills among School Administrators of Public Higher Education Institutions in Sulu - Anuddin, Fermina Omar (Future Science / FSH-PH Publications, 2025)
This descriptive-correlational study investigates the extent of conflict management and decision-making skills among public higher education institution administrators in Sulu for the Aca-demic Year 2022-2023. The respondents in this study are 200 fac-ulty members, with several statistical methods applied, including frequency counts, percentages, weighted means, standard devia-tions, t-tests for independent samples, One-way ANOVA, and Pear-son's r.Most respondents were between 20 and 35 years old, female, married, and holding a master's degree. Many faculty members reported having served from 1 to 15 years in their respective insti-tutions. In fact, the respondents agreed that the administrators were pretty successful in getting faculty involved in key decisions concerning the institutions. They also graded the administrators as vigilant and decisive when dealing with sensitive and critical matters.Interestingly, differences in ratings regarding the faculty's evaluation of administrators' skills for conflict management and decision-making by age, gender, civil status, educational attain-ment, and years of service do not indicate statistical significance. But those who have high grades of administrators for the man-agement of conflict also graded highly the ability to make deci-sions. This study supports Rahim's (2002) proposition that suc-cessful conflict management is made of multiple strategies. Thus, those administrators who make effective decisions on handling conflicts would tend to be good decision-makers.Finally, it has underlined that to achieve better and sound deci-sion making as well as better management of the institutions in conflict management is needed to become good administrators. Therefore, good administrative leadership does not only work well to facilitate more effectiveness of its own work but also enables more harmony and effectiveness within a higher education public institution. More emphasis needs to be made upon their skill im-provement.